Ma’ānī Harf al-Waw wa Fawāiduhā fī Ṣūraṭi al-Kahf (Dirāsah Taḥlīliyyah Naḥwiyyah Lughawiyyah) - Farid, Farid; Bamualim, Mubarak; Fahamsyah, Fadlan (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study aims to understand the meanings of the letter waw in Surah Al-Kahf and to explore the benefits of these meanings in comprehending the stylistic aspects of the Noble Quran. Regarding the methodology of this humble research, the researcher employed a qualitative approach. The study is classified as library research, with data collection tools consisting of documents and observations. As for data analysis, the researcher utilized a qualitative analysis method by referring to both classical and contemporary references and sources related to the Arabic language and its grammatical rules.One of the findings of this research is that the researcher identified four types of meanings associated with the letter waw in Surah Al-Kahf: circumstantial (ḥāliyyah), coordinating (‘āṭifah), resuming (isti’nāfiyyah), and parenthetical (i‘tirāḍiyyah). The opinions of esteemed grammarians show slight differences regarding the parsing of certain words in the Noble Quran. An example of this can be seen in the verse: {الْحَمْدُ لِلَّهِ الَّذِي أَنْزَلَ عَلَى عَبْدِهِ الْكِتَابَ وَلَـمْ يَجْعَلْ لَهُ عِوَجًا}, where the phrase {وَلَـمْ يَجْعَلْ لَهُ عِوَجًا}  demonstrates that the letter waw has multiple possible grammatical interpretations: some classify it as coordinating (‘āṭifah), others as parenthetical (i‘tirāḍiyyah), and others as circumstantial (ḥāliyyah).The reason for these variations lies in the nature of the Arabic language, which allows for multiple syntactic interpretations, as well as in the different perspectives from which expert grammarians analyze context and meaning. This highlights the richness of the eloquent Arabic language and the depth of grammatical thought that has been dedicated to serving the Quranic text with the highest level of precision and care.